ELECTRONIC GAMING SYSTEM WITH CODEGUARD (2013)
Examples disclosed herein relate to systems and methods for validating the authenticity of one or more media associated with a gaming system. The systems and methods may utilize a RAM-based algorithm to validate such media. Further, the RAM-based algorithm by utilize a dirty bit validation procedure to validate the media.